Cargas superficiais da fração argila de solos influenciadas pela vinhaça e fósforo - Ribeiro,Bruno Teixeira (2011)
Effects of vinasse, P sorption and the interaction vinasse-phosphorus on zeta potential and point of zero charge (PZC) as well as the effects of vinasse on P sorption on clay-fraction samples from two soils were evaluated. The vinasse and P sorption influenced the surface charge of clay fraction of both soils. Sorption of P increased negative charges from soil particles reducing PZC. These effects were more pronounced when clay fraction was previously treated with vinasse. Vinasse treatment reduced P sorption, probably due to coating of P-adsorption sites and by enhancing the negative charges.